Assessment of race and sex as risk factors for colonization with multidrug-resistant organisms in six nursing homes. (4th October 2020) - Gontjes, Kyle J.; Gibson, Kristen E.; Lansing, Bonnie J.; Mody, Lona; Cassone, Marco
Abstract: The role of demographic characteristics, such as sex and race, as risk factors for colonization with multidrug-resistant organisms, has not been established in the nursing home setting. We demonstrate significantly higher prevalence overall in male patients, and sex differences are dependent on organism of interest and body site.